PENGARUH MANAJEMEN KUALITAS DAN INOVASI TERHADAP KEUNGGULAN BERSAING DAN KINERJA USAHA LEMPUK DURIAN DI KABUPATEN BENGKALIS - Agtivo Ivonny; Daulay Nauli Iwan; Siregar Andreas Prima (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of quality management andinnovation on competitive advantage and business performance lempuk durian inBengkalis District. The population of study included all lempuk durian business inBengkalis District were 58 units and sampling technique used was saturationsampling. Structural Equation Model (SEM) with SmartPLS version 3 was used asmethods of data analysis. The results were: 1) Quality management had a positiveand significant effect on competitive advantage; 2) Innovation had a positive andsignificant effect on competitive advantage; 3) Quality management had a positiveand significant effect on business performance; 4) Innovation had a positive andsignificant effect on business performance; 5) Competitive advantage had apositive and significant effect on business performance; 6) Quality managementhad a positive and significant effect on business performance throughworkcompetitive advantage; 7) Innovation had a positive and significant effect onbusiness performance throughwork competitive advantage. Keyword: Quality Management, Innovation, Competitive Advantage, BusinessPerformance.